ANALISIS MANAJEMEN RISIKO PADA BENDUNGAN - Yusrizal Muhiddin; M. Agung Wibowo; Lalu Makruf (JURNAL ILMIAH NUSANTARA, 2024)
Dams are structures in the form of earth embankments, rock embankments, and concrete, which are built in addition to holding and storing water, can also be built to hold and store mining waste, or store mud so that a reservoir is formed. One of the jobs on the dam is plugging work. Plugging is the work of blocking the diversion channel with concrete. The aim is to block the river flow so that the dam is filled with water. Dam construction projects in their implementation methods have characteristics of complicated and complex work, so they are very susceptible to risks in construction implementation. In construction projects, risks cannot be eliminated. The purpose of this study is to determine the risks that may occur in the Tapin Dam Construction project. The method in this study is to use the Severity Index method and interviews. The results of this study were 19 risks in the Tapin Dam Plugging Work project. These risks are divided into three categories, including high risk, medium risk and low risk.